Critical review: “The singing neanderthals: the origins of music, language, mind, and body” - Fornari, José (Revista Hipótese, 2022)
This critical review is a fascinating work by Mithen on the willingness of humans to make and listen to music. Language and music are probably restricted to Homo sapiens, but musicality originates in our hominid ancestors and relatives. Mithen seeks explanations associated with language and music by bringing together theoretical insights from archaeology, anthropology, biology, neuroscience, and musicology to develop a sophisticated understanding of pre-modern communication systems of what currently exists. The work explains how the ability for music has evolved by addressing the evolution of language, body, and mind.
Keywords: Homo Sapiens; Musicality; Language evolution